2009
DOI: 10.1002/eji.200939543
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination with an adenoviral vector encoding the tumor antigen directly linked to invariant chain induces potent CD4+ T‐cell‐independent CD8+ T‐cell‐mediated tumor control

Abstract: Antigen-specific immunotherapy is an attractive strategy for cancer control. In the context of antiviral vaccines, adenoviral vectors have emerged as a favorable means for immunization. Therefore, we chose a strategy combining use of these vectors with another successful approach, namely linkage of the vaccine antigen to invariant chain (Ii). To evaluate this strategy we used a mouse model, in which an immunodominant epitope (GP33) of the LCMV glycoprotein (GP) represents the tumor-associated neoantigen. Proph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(50 citation statements)
references
References 37 publications
(47 reference statements)
3
46
1
Order By: Relevance
“…Most important, in both experimental setups, tumor control was limited compared with that observed in mice vaccinated with Ad-Ii-GP, thus targeting a non-self-Ag. It is generally acknowledged that CD8 T cells are key players in immune-mediated tumor degradation, and our previous studies have also demonstrated that the Ad-Ii-GP-induced tumor control is dependent on an improved CD8 T cell response as well as IFN-g (16). Thus, we concluded that the reason for the difference in tumor control had to reflect differences in numbers and/or quality of vaccine-induced CD8 T cells depending on their specificity for selfversus non-self-Ags.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Most important, in both experimental setups, tumor control was limited compared with that observed in mice vaccinated with Ad-Ii-GP, thus targeting a non-self-Ag. It is generally acknowledged that CD8 T cells are key players in immune-mediated tumor degradation, and our previous studies have also demonstrated that the Ad-Ii-GP-induced tumor control is dependent on an improved CD8 T cell response as well as IFN-g (16). Thus, we concluded that the reason for the difference in tumor control had to reflect differences in numbers and/or quality of vaccine-induced CD8 T cells depending on their specificity for selfversus non-self-Ags.…”
Section: Discussionmentioning
confidence: 83%
“…Generally, viruses seem to induce exactly the type of immune response that would be expected to be optimal for efficient tumor control. Consequently, having established an improved platform for anti-infective vaccination using a replication deficient adenovirus, Ad-Ii-GP, we previously tested this vector against tumor cells expressing a viral epitope, namely the LCMV GP (33), and found significant protection (16,59). Notably, this was the case even in hosts expressing the targeted viral epitope as a self-Ag in the pancreas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Absence of a dominant epitope in an Ii-linked construct may dramatically increase subdominant responses Linking the vaccine Ag expressed from an adenoviral vector to the MHC class II-associated Ii has proved successful in eliciting increased numbers of Ag-specific CD8 + T cells in several studies (29,30,(35)(36)(37). However, the effect of Ii linkage varies with the selected Ag, and we have previously observed that the NP of LCMV does not seem to benefit from Ii linkage in terms of numbers of NP396 (dominant epitope)-specific CD8 + T cells and protection from LCMV infection (24) (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%